Leptin and brain–adipose crosstalks - Caron, Alexandre (Nat Rev Neurosci, 2018)
Interactions between the brain and distinct adipose depots have a key role in maintaining energy balance, thereby promoting survival in response to metabolic challenges such as cold exposure and starvation. Recently, there has been renewed interest in the specific central neuronal circuits that regulate adipose depots. Here, we review anatomical, genetic and pharmacological studies on the neural regulation of adipose function, including lipolysis, non-shivering thermogenesis, browning and leptin secretion. In particular, we emphasize the role of leptin-sensitive neurons and the sympathetic nervous system in modulating the activity of brown, white and beige adipose tissues. We provide an overview of advances in the understanding of the heterogeneity of the brain regulation of adipose tissues and offer a perspective on the challenges and paradoxes that the community is facing regarding the actions of leptin on this system.